The plasma contact system as a modulator of innate immunity - Wu, Yi (Current opinion in hematology, 2018)
The contact system is a plasma protease cascade, which activates the proinflammatory kallikrein-kinin system and the procoagulant intrinsic coagulation pathway. Recent advances demonstrating the novel functions of this system as a key player of innate immune system will be introduced in the present review. The role of the contact system is to initiate and participate in pathophysiological responses to injury, mainly the processes of coagulation and inflammation. The past few years have seen substantial progress, showing a new role of this system in regulation of innate immunity. The relationship between high-molecular-weight kininogen and lipopolysaccharide (LPS) has been investigated and a new function of high-molecular-weight kininogen has been identified as the critical LPS carrier supporting endotoxemia. In contrast, the role of high-molecular-weight kininogen in Klebsiella pneumoniae sepsis is limited. Coagulation factor XII (FXII) plays a detrimental role in murine wound healing and host defense against K. pneumoniae sepsis. In the pathogenesis of arthritis and colitis, the activation of plasma kallikrein and downstream cleavage of high-molecular-weight kininogen and release of bradykinin constitutes a critical pathway in the innate immune mechanism, whereas FXII is not important. Current findings indicate that the plasma contact system functions as an important constituent of innate immune system, contributing to the pathogenesis of the immunological and infectious diseases.